Photocatalytic Hydrogen Production from Homo- and Hetero-geneous Cobalt (II) Catalysts - Sharif, Ayni (Université d'Ottawa | University of Ottawa, 2020)
Various energy sources on which society depends are rapidly depleting in recent years. Alternate fuel sources that are cost efficient, earth abundant, and easily accessible has been urgently sought out by numerous researchers worldwide. Hydrogen represents an excellent target that could meet these pressing needs. This project has identified efficient photocatalytic production of hydrogen from the reduction of water using both homo- and hetero-geneous cobalt (II) complexes. A pincer selenium-nitrogen ligand scaffold, 2,6-bis[(pyrazol-1-yl)methyl]pyridine, was used to support a potential homogeneous catalyst. However, the formation of precipitates during catalytic process raised concerns over certainty of the activity of the homogeneous catalyst. These concerns prompted the investigation of cobalt oxide nanoparticles as potential heterogeneous catalysts. These explorations revealed this system to be a much more efficient catalyst through visible-light photochemistry of reducing water for hydrogen production in the presence of a Ru(bpy)3[2+] photosensitizer and a reductant.
Keywords: hydrogen; carbon dioxide; nanoparticle; catalyst